2022
DOI: 10.1017/s0007114522000125
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D impacts on the intestinal health, immune status and metabolism in turbot (Scophthalmus maximus L.)

Abstract: Vitamin D (VD) plays a vital role in various physiological processes in addition to its classic functions on maintaining the balance of calcium and phosphorus metabolism. However, there still are gaps to understand in depth the issues on the precise requirement, metabolic processes, and physiological functions of VD in fish. In this study, we investigated the effects of VD on the growth, intestinal health, host immunity and metabolism in turbot (Scophthalmus maximus L.), one important commercial carnivorous fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Previous results both from others and from our research group have demonstrated that VD 3 significantly impacts the glucose metabolism in higher animals 17 and fish 28 . It is well‐known that insulin is one of the most important hormones to maintain glucose homeostasis 29 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous results both from others and from our research group have demonstrated that VD 3 significantly impacts the glucose metabolism in higher animals 17 and fish 28 . It is well‐known that insulin is one of the most important hormones to maintain glucose homeostasis 29 .…”
Section: Discussionmentioning
confidence: 58%
“…More importantly, our results have demonstrated Previous results both from others and from our research group have demonstrated that VD 3 significantly impacts the glucose metabolism in higher animals 17 and fish. 28 It is well-known that insulin is one of the most important hormones to maintain glucose homeostasis. 29 Meanwhile, insr is a key element in insulin signaling pathway, and insulin/insr interaction serves to amplify and diversify insulin actions.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for the discrepancy in C proteins across studies may be as follows: First, the settings of the control groups in each study are not uniform (generally, the control group is VD 3 deficiency or the minimum demand of VD 3 in this species). If the controls are VD 3 deficient, it may cause more serious inflammation in the fish body 51,66 . Second, fish C protein gene is not only expressed in the liver, but also in brain, intestine, kidney, gill, skin, gonad and other organs, and participates in the body fluid, lymph and blood circulation 93 .…”
Section: Physiological Function Of Vd3 In Fishmentioning
confidence: 99%
“…According to Darias et al, dietary VD 3 can promote the maturation of the intestinal digestive function of European sea bass and enhance the activity of digestive enzymes 82 . A new study showed that dietary VD 3 deficiency decreased the gut microbial population of turbot, while the abundance of beneficial bacteria such as Lactobacilli increased in the VD 3 ‐sufficient group 66 …”
Section: Physiological Function Of Vd3 In Fishmentioning
confidence: 99%
See 1 more Smart Citation